IMPROVEMENT PROPOSALS FOR CULTURE METHODS TO DIAGNOSIS OF PROSTHETIC JOINT INFECTIONS IN LATIN AMERICA - Ivalde, Flavio César; Yeimer, Ortiz-Martinez; Andrea, Buelvas-Perez (Journal of Ayub Medical College Abbottabad, 2019)
Different diagnostic and treatment algorithms for prosthetic infections of the hip and knee are available and widely used in North America. However, for the best of our knowledge, the sampling methodology in Latin American countries is not protocolized varying among the members of the region. In conclusion, we recommend that samples should aim to screen for aerobic, anaerobic, mycobacterial, fungal, and intracellular bacteria. These recommendations are based on experience, especially in Latin America. Further research is necessary for the realization of an international consensus.